A Tathwīr Kitāb Durūs al-Lughah al-'Arabiyah Juz' al-Awwal bi Dhau'i al-Mahārāt al-Lughawiyah - Ami, Fikriah Islami; Fajriyani Arsya, Fajriyani Arsya (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Based on the objectives of learning Arabic in this institute, students are required to be more active in speaking Arabic, not only that students are also required to be proficient in listening, reading and writing in Arabic. In addition to learning Arabic today, students are required to master four skills in the Arabic language. However, judging from the background of this book, it only focuses on Arabic communication practice, while the other three skills are not presented. Based on that, the researcher wanted to develop this book "Arabic Language Lessons Part One" to help students to know the four language skills. The research method used by the researcher is developmental research. The research chose the development research based on the ADDIE, which consists of five stages analysis, design, development, implementation, and evaluation. The researcher obtained the conclusion of this research is suitable for use in the process of learning the Arabic language, and this conclusion is that the average of the results of the questionnaire from experts upon investigation and from students upon implementation is 80%. According to Likert scales, this result is on a “good” scale, so the production was appropriate for the process of learning the Arabic language.